The effect of corporate brand dominance, involvement and corporate associations on attitudes toward new product development - Hsin, Hsin Chang; Mohamad Rizal Abdul Hamid (Academic Journal, 2011)
This study investigates the moderating role of corporate brand dominance and involvement in the relationship between corporate associations and attitudes toward new product. An experiment design using two version of advertisements are developed to manipulate the corporate brand dominance. A skincare product manufactured by a Taiwan petrochemical company was used in the study. The results indicate that both associations of corporate ability and corporate credibility have greater effect on consumer attitudes toward new product than corporate social responsibility. However, there are no significant relations between corporate brand dominance and involvement in both of these associations (corporate ability and corporate credibility). Instead, there are significant moderation effects between corporate brand dominance and involvement in corporate social responsibility. Implications for future research are discussed and limitations noted.